Additive manufacturing low alloy steel and preparation method thereof

By precisely controlling the components and heat treatment processes of additive manufacturing low-alloy steels, a cellular partially polymerized martensite or bainite/martensite complex phase structure is formed, which solves the problems of high cost and insufficient strength of steel in additive manufacturing, and achieves a matching of high strength and good plasticity.

CN119776743APending Publication Date: 2025-04-08CHINA IRON & STEEL RESEARCH INSTITUTE GROUP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411972927.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Existing high-strength steels are costly and have insufficient strength, especially in additive manufacturing, which are prone to strength reduction problems caused by cracks and alloy elements segregation.

Method used

By precisely controlling the components and preparation methods of additively manufactured low-alloy steel, including alloy elements ratio and heat treatment process, we form a cellular partially polymerized martensite or bainite/martensite complex phase structure, combined with high-temperature and low-temperature tempering treatment, the phase change behavior during the cooling process is controlled and the structure is refined.

Benefits of technology

It has achieved a significant improvement in material strength and plastic matching under a lower alloy ratio, reducing material cost, tensile strength ≥1834MPa, yield strength ≥1350MPa, and elongation after break ≥10%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119776743A_ABST
    Figure CN119776743A_ABST
Patent Text Reader

Abstract

The present invention relates to an additively manufactured low alloy steel and a preparation method thereof, which belongs to the technical field of high-strength alloy steel and solves the problems of high cost and insufficient strength of existing high-strength steel. The components of the additively manufactured low alloy steel are calculated by mass percentage as follows: C: 0.25% to 0.30%, Mn: 0.4% to 0.7%, Si: 0.8% to 1.2%, Cr: 2.4% to 2.8%, Ni: 0.8% to 1.2%, Mo: 0.8% to 1.1%, W: 0.1% to 0.3%, Nb≤0.02%, Al≤0.01%, Ti:≤0.03%, Zr≤0.02%, and the remainder is Fe and unavoidable impurities. The additively manufactured low alloy steel of the present invention achieves low raw material cost and good strength-plasticity matching.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of high-strength alloy steel, and in particular to an additively manufactured low-alloy steel and a preparation method thereof. Background Art

[0002] Key components in aerospace and other fields have extremely high requirements for material properties, especially requiring materials to have ultra-high strength. Higher C elements or more alloying elements such as Cr, Ni, Co, and Mo are important factors in improving the strength of steel materials. However, for additive manufacturing of complex components, more C elements are prone to cause cracks, while higher alloying elements will greatly increase the cost of the alloy. At present, high strengthening of additive manufacturing of medium- and low-carbon low-alloy steels is a hot issue in the development of this type of material. Summary of the invention

[0003] In view of the above analysis, the present invention aims to provide an additively manufactured low alloy steel and a preparation method thereof, so as to solve at least one of the following problems: the existing high strength steel has high cost and insufficient strength.

[0004] The purpose of the present invention is mainly achieved through the following technical solutions:

[0005] On the one hand, the present invention provides an additively manufactured low-alloy steel, wherein the components of the additively manufactured low-alloy steel are, by mass percentage, C: 0.25% to 0.30%, Mn: 0.4% to 0.7%, Si: 0.8% to 1.2%, Cr: 2.4% to 2.8%, Ni: 0.8% to 1.2%, Mo: 0.8% to 1.1%, W: 0.1% to 0.3%, Nb≤0.02%, Al≤0.01%, Ti:≤0.03%, Zr≤0.02%, and the balance is Fe and unavoidable impurities.

[0006] Furthermore, in the components of additively manufactured low alloy steel, the Cr / Ni value is controlled to be 2.5 to 2.8.

[0007] Furthermore, the microstructure of the additively manufactured low alloy steel consists of martensite or bainite / martensite duplex structure with alloy cellular segregation.

[0008] Furthermore, there is cellular segregation of alloy elements in the microstructure of the additively manufactured low-alloy steel, with the Cr content at the cell wall being ≥3.0% and the Mo content being ≥1.1%.

[0009] The present invention also provides a method for preparing the above-mentioned additively manufactured low-alloy steel, comprising:

[0010] Step S1: preparing powder;

[0011] Step S2: using laser melting deposition to perform additive manufacturing on the parts, using high-purity argon as the protective gas; after each deposition of a certain thickness, the material is left to cool to room temperature before deposition is performed again;

[0012] Step S3: Cooling the printed sample to room temperature after high temperature isothermal treatment;

[0013] Step S4: subjecting the printed sample to low-temperature annealing treatment.

[0014] Furthermore, in step S3, the high temperature isothermal treatment includes: keeping warm at 930°C to 980°C.

[0015] Furthermore, in step S3, during the cooling process, the cooling rate in the temperature range of 850 to 350°C is controlled to be ≥1°C / s; the cooling rate in the temperature range of 350°C to 150°C is controlled to be 0.5°C to 5°C / s.

[0016] Furthermore, in step S4, the low-temperature tempering temperature is controlled to be 210°C to 230°C.

[0017] Furthermore, in step S1, a plasma rotating electrode method is used to prepare powder, and the powder particle size is controlled to be 50 to 160 μm.

[0018] Furthermore, in step S2, during the printing process, the laser power is 1400-1800W.

[0019] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:

[0020] 1. The additively manufactured low-alloy steel of the present invention improves the coarse oxides caused by oxygen addition in the additive manufacturing process by precisely controlling the content of each element, especially by adding Al, Ti, and Zr, and the composite micro-alloyed oxides are refined, thereby ensuring that the additively manufactured low-alloy steel of the present invention has good strength-plasticity matching.

[0021] 2. In the preparation method of the present invention, additive manufacturing is adopted, combined with high-temperature isothermal and low-temperature tempering processes, and the cooling process after high-temperature isothermal is precisely controlled, so as to effectively utilize additive manufacturing to form cellular segregation. By matching a reasonable heat treatment method, the cellular segregation is utilized to limit the phase transformation, so that the martensitic phase transformation or bainitic phase transformation in the cooling process is changed from being controlled by the original austenitic grain size to being controlled by the cellular segregation size. The preparation method can greatly improve the material strength.

[0022] 3. The present invention achieves high strength effect under the condition of lower alloy ratio and reduces material cost by rationally controlling the phase change behavior during cooling process of Cr and Ni elements.

[0023] 4. The microstructure of the additively manufactured low alloy steel of the present invention is composed of martensite or bainite / martensite multiphase structure with alloy cell segregation. The substructure size of martensite or bainite / martensite multiphase structure is significantly refined, and the strength and plasticity of the material are further improved, for example, the length of the lath is 5 to 35 μm. The Cr content at the cell wall is ≥3.0%, and the Mo content is ≥1.1%. The additively manufactured low alloy steel of the present invention has excellent performance, for example, tensile strength ≥1834MPa (for example, 1834 to 1880MPa); yield strength ≥1350MPa (for example, 1354 to 1480MPa); elongation after fracture ≥10% (for example, 10.1% to 12.1%).

[0024] In the present invention, the above-mentioned technical solutions can also be combined with each other to achieve more preferred combination solutions. Other features and advantages of the present invention will be described in the subsequent description, and some advantages can become obvious from the description, or can be understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained through the contents particularly pointed out in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] The drawings are only for the purpose of illustrating specific embodiments and are not to be considered limiting of the present invention. Like reference symbols denote like components throughout the drawings.

[0026] Figure 1 is a microstructure morphology diagram of Example 1 of the present invention;

[0027] Figure 2 is an electron backscattering image of Example 1 of the present invention;

[0028] Figure 3 It is the electron backscattering image of comparative example 1 of the present invention. DETAILED DESCRIPTION

[0029] The preferred embodiments of the present invention will be described in detail below in conjunction with the accompanying drawings, wherein the accompanying drawings constitute a part of the present invention and are used together with the embodiments of the present invention to illustrate the principles of the present invention, but are not used to limit the scope of the present invention.

[0030] Different from the traditional forged structure, the additive manufacturing process will lead to an increase in the oxygen content of the alloy on the one hand, and cellular segregation of alloy elements on the other hand. For medium-low carbon low-alloy martensitic steel, the increase in oxygen content will lead to an increase in material oxides and a decrease in plastic toughness; cellular segregation will lead to a decrease in matrix alloy content, a weakening of the alloy solid solution strengthening effect, and a decrease in material strength; currently, it is usually necessary to eliminate cellular segregation through high-temperature homogenization treatment (≥1000℃), which makes the austenite grains coarse and the material strengthening effect weakened. Therefore, it is urgent to develop a low-cost low-alloy system of ultra-high strength steel, matching a suitable preparation method, to obtain good strength improvement.

[0031] The present invention provides an additively manufactured low-alloy steel, wherein the components of the additively manufactured low-alloy steel are, by mass percentage, C: 0.25% to 0.30%, Mn: 0.4% to 0.7%, Si: 0.8% to 1.2%, Cr: 2.4% to 2.8%, Ni: 0.8% to 1.2%, Mo: 0.8% to 1.1%, W: 0.1% to 0.3%, Nb≤0.02%, Al≤0.01%, Ti≤0.03%, Zr≤0.02%, and the remainder is Fe and unavoidable impurities.

[0032] Specifically, in the composition of the additively manufactured low alloy steel, Cr+Ni≤4%, 2.5≤Cr / Ni≤2.8 are controlled.

[0033] The functions and dosages of the components in the present invention are described in detail below.

[0034] Carbon (C): Carbon is an important interstitial solid solution strengthening element that can adjust the alloy martensite and bainite phase transformation temperature range; at the same time, carbon can also stabilize the presence of residual austenite. However, too high a carbon content can easily lead to cracking behavior in the additive manufacturing process. Therefore, under the premise of ensuring the strength of the material, the high density of the additively manufactured ultra-high strength steel should be ensured. After comprehensive consideration, the carbon content is controlled at 0.25% to 0.30% in the present invention.

[0035] Manganese (Mn), chromium (Cr), nickel (Ni): The content of manganese, chromium and nickel in the alloy is used to control the hardenability of the material. Manganese is a low-cost solid solution strengthening element that can improve the stability of austenite, but too high a manganese content may lead to element segregation. Therefore, when adding manganese to the alloy, it is also necessary to control the content of chromium and nickel, controlling Cr+Ni≤4%, and 2.5≤Cr / Ni≤2.8. Chromium and nickel elements can enhance the toughness of the material; in addition, manganese and chromium elements are also the main segregation elements in the cellular segregation in additive manufacturing, which is caused by the rapid solidification process of the additive manufacturing micro-region; at the same time, manganese and chromium elements are also important elements that affect the thermodynamics of martensite and bainite phase transformations. Micro-regions with high manganese and chromium content can effectively hinder the growth of martensite or bainite laths; nickel elements can improve the stability of austenite and improve the plasticity and toughness of the alloy, but its economic efficiency is poor. Taking all factors into consideration, in the present invention, the content of manganese is controlled within the range of 0.4% to 0.7%, the content of chromium is controlled within the range of 2.4% to 2.8%, and the content of nickel is controlled within the range of 0.8% to 1.2%.

[0036] Silicon (Si): The addition of silicon can inhibit the precipitation of cementite during cooling and tempering, improve tempering resistance, and expand the precipitation range of ε-carbide, which helps the material maintain a high strength without reducing plasticity; in addition, silicon can also assist the bainite phase transformation morphology, refine the bainite laths, and improve the matrix strength. Therefore, in the present invention, the silicon content is controlled at 0.8% to 1.2%.

[0037] Molybdenum (Mo) and tungsten (W): The addition of molybdenum and tungsten can play a role in solid solution strengthening and purify the austenite grain boundaries, thereby delaying the transformation of bainite. Molybdenum is also a solidification segregation element. The segregation of molybdenum at the cell wall can further reduce the nucleation temperature of martensite or bainite nucleated at the cell wall. At the same time, compared with the forged alloy, the specific surface area of ​​the additive manufacturing powder is increased, and the contact surface with the hydrogen-containing environment is larger. The addition of molybdenum and tungsten can also improve the hydrogen embrittlement sensitivity of additively manufactured ultra-high strength steel and improve the hydrogen embrittlement resistance of the deposited alloy. The addition of too much tungsten and molybdenum elements will also increase the solidification temperature range of the alloy and increase the risk of thermal cracking of the additive alloy. Therefore, in the present invention, the molybdenum element is controlled at 0.8% to 1.1% and the tungsten element is controlled at 0.1% to 0.3%.

[0038] Niobium (Nb): Niobium is an important microalloying element that produces nano-precipitation strengthening in the rapid solidification process and slow cooling process of additive manufacturing. At the same time, niobium can also inhibit the coarsening of grains during austenitization and improve the performance consistency of the material. Therefore, in the present invention, the content of niobium should be controlled at ≤0.02%.

[0039] Aluminum (Al), titanium (Ti), zirconium (Zr), for the heat treatment process of traditional alloys, aluminum and titanium elements are easy to combine with nitrogen to form coarse precipitation that is detrimental to the plasticity and toughness of the material. However, compared with traditional casting and forging alloys, additive manufacturing alloys will inevitably have a significantly increased oxygen content. Compared with the coarse alumina or silicates that are easy to form, adding a small amount of titanium and zirconium elements to the alloy can form ultrafine aluminum-titanium-zirconium composite oxides, achieve significant refinement of the oxides, and improve the plasticity and toughness of the additive manufacturing alloy while increasing the strength of the material. However, the addition of too much aluminum-titanium-zirconium alloy will combine with other elements in the matrix to form a brittle phase. In view of the characteristic that the oxygen content of the additive manufacturing alloy is about 100ppm to 500ppm, the matching aluminum-titanium-zirconium element content in the present invention is controlled at Al≤0.01%, Ti≤0.03%, and Zr≤0.02%, respectively.

[0040] In order to further improve the comprehensive performance of the above-mentioned additively manufactured low-alloy steel, the components of the above-mentioned additively manufactured low-alloy steel are calculated by mass percentage as follows: C: 0.26%~0.295%, Mn: 0.45%~0.65%, Si: 0.85%~1.1%, Cr: 2.5%~2.8%, Ni: 0.85%~1.15%, Mo: 0.9%~1.1%, W: 0.1%~0.25%, Nb: 0.005%~0.015%, Al: 0.005%~0.015%, Ti: 0.01%~0.03%, Zr: 0.005%~0.02%, and the balance is Fe and unavoidable impurities.

[0041] Specifically, in the components of the additively manufactured low alloy steel, the value of Cr+Ni is 3.5% to 3.8%, and the value of Cr / Ni is 2.5 to 2.75.

[0042] The present invention also provides a method for preparing additively manufactured low alloy steel, which is used to prepare the additively manufactured low alloy steel, comprising the following steps:

[0043] Step S1: preparing powder;

[0044] Step S2: Additive manufacturing, using laser melting deposition (LMD) to perform additive manufacturing on the parts, using high-purity argon as a protective gas; after each deposition of a certain thickness, the material is left to cool to room temperature before deposition is performed again;

[0045] Step S3: The printed sample is kept at 930° C. to 980° C. for high temperature isothermal treatment and then cooled to room temperature;

[0046] Step S4: subjecting the printed sample to low temperature tempering treatment at 200°C to 240°C.

[0047] Specifically, in step S1, the powder is prepared by a plasma rotating electrode method. Considering that too large a particle size of the powder will result in incomplete melting, and too small a particle size will affect the powder deposition efficiency and dispersion, the powder particle size is controlled to be 50 to 160 μm.

[0048] Specifically, in step S2, considering that in the printing process, too high laser power will lead to too large a molten pool, large grain size and molten pool collapse, too low will lead to poor powder fusion; too high scanning speed will easily lead to unmelted powder, too low will affect the deposition efficiency and cause overburning of materials. Therefore, the laser power is controlled to be 1400-1800W, such as 1500W, 1600W, 1700W, and the scanning speed is 4-6mm / s, such as 4.5mm / s, 5mm / s, 5.5mm / s.

[0049] Specifically, in step S2, the overlap rate is controlled to be 45% to 55%.

[0050] Specifically, in step S2, after each deposition of 2 to 4 cm in thickness, the material is left to cool to room temperature before deposition is performed again, so as to avoid excessive internal stress in the material due to simultaneous martensitic transformation when multiple layers of the material are heated and finally cooled.

[0051] Specifically, in step S2, the above printing process is used to make the density of the parts reach more than 99.9% without generating thermal cracks.

[0052] Specifically, in step S3, if the holding temperature is too high, the diffusion of alloy elements and the coarsening of austenite grains will be accelerated. If the holding temperature is too low, the austenitization cannot be completely completed or some carbides are not completely melted back. If the holding time is too long, it is easy to cause the diffusion of cellular segregated alloy elements. Therefore, the temperature is controlled at 930°C to 980°C (for example, 940°C, 950°C, 960°C, 970°C) for 10 to 60 minutes.

[0053] Specifically, in step S3, considering that during the cooling process after high temperature isothermal treatment, in the temperature range of 850-350°C, a slower cooling rate may cause carbide precipitation, ferrite transformation or coarse bainite transformation, the cooling rate in this temperature range is required to be ≥1°C / s. The temperature range of 350℃~150℃ is the phase transformation range of martensite or lower bainite of the material. The supercooling control in this phase transformation range can control whether the bainite or martensite phase transformation penetrates the range of cellular segregation and grows, thereby controlling the strength of the matrix structure. If the cooling rate in this stage is too fast (>5℃ / s), the supercooling of the martensite phase transformation will be too high. The phase transformation process occurs simultaneously in the cell and the cell wall, and the martensite laths grow through the cell wall. This will cause the martensite laths to be coarse. Although a full martensite structure can be formed, its strength is not fully optimized. If the cooling rate is too slow (<0.5℃ / s), bainite will be formed in the high temperature range. In the high temperature range, the generated bainite laths have the conditions to penetrate the alloy-enriched area of ​​cellular segregation, which causes the structure in the cell and at the cell wall to soften at the same time, and finally causes the softening of the matrix and insufficient strength. Therefore, the cooling rate in the temperature range of 850-350°C is controlled to be ≥1°C / s; the cooling rate in the temperature range of 350°C-150°C is controlled to be 0.5°C-5°C / s.

[0054] Preferably, the cooling rate in the temperature range of 850-350°C is 1-4°C / s, and the cooling rate in the temperature range of 350°C-150°C is 0.5-2°C / s.

[0055] Specifically, in step S4, the low temperature tempering process can further improve the strength-plasticity matching of the ultra-high strength steel. In the present invention, the low temperature tempering temperature is controlled to be 210°C to 230°C, and the tempering time is 1 to 2 hours, which can avoid coarse carbides and meet the tempering requirements of the overall parts.

[0056] In the prior art, cellular segregation is usually not conducive to the strength of ultra-high strength steel. The main reason is that although the segregated elements can enhance the solid solution strengthening effect of the cell wall position, the alloy depletion of the intracellular structure, which accounts for the vast majority of the volume fraction, may reduce the overall strength of the alloy. Therefore, it is usually necessary to undergo high-temperature diffusion treatment to eliminate cellular segregation. However, high-temperature treatment is usually accompanied by the growth of austenite grains, and the material strengthening effect is weakened. The present invention prepares additive manufacturing low-alloy steel through the precise design of alloy components, the optimization of the preparation process, and the precise control of process parameters. The present invention adopts the design of controlled addition of Al, Ti, and Zr oxide alloys to improve the coarse oxides caused by oxygen addition in the additive manufacturing process, and the composite micro-alloyed oxides are refined. The present invention effectively utilizes additive manufacturing to form cellular segregation, and by matching a reasonable heat treatment process, the phase transformation is limited by cellular segregation, so that the martensitic phase transformation or bainitic phase transformation in the cooling process is controlled by the original austenitic grain size and is controlled by the cellular segregation size. The control method can greatly improve the strength of the material. The present invention achieves high strength effect under the condition of relatively low alloy ratio and reduces material cost by reasonably controlling the Cr and Ni elements to regulate the phase change behavior during the cooling process.

[0057] Specifically, the microstructure of the additively manufactured low alloy steel prepared by the method of the present invention is composed of a martensite or bainite / martensite multiphase structure with alloy cell segregation. Cellular segregation can effectively limit the growth of martensite or bainite laths within the cell, thereby achieving a new control over the substructure size in the microstructure.

[0058] Specifically, in the microstructure of the additively manufactured low alloy steel of the present invention, the substructure size of the martensite or martensite / martensite complex structure is significantly refined, and the strength and plasticity of the material are further improved, for example, the lath length is 5 to 35 μm.

[0059] Specifically, in the additively manufactured low-alloy steel prepared by the method of the present invention, the Cr element content at the cell wall is ≥3.0%, and the Mo element content is ≥1.1%.

[0060] The additively manufactured low alloy steel of the present invention has excellent properties, for example, tensile strength ≥1834MPa (for example, 1834-1880MPa); yield strength ≥1350MPa (for example, 1354-1480MPa); elongation after fracture ≥10% (for example, 10.1%-12.1%).

[0061] The advantages of precise control of the composition and process parameters of the steel of the present invention are demonstrated below with specific examples and comparative examples.

[0062] Example 1

[0063] This embodiment provides an additively manufactured low alloy steel and a preparation method thereof. The components of the steel in this embodiment are shown in Table 1 below. The preparation method includes:

[0064] (1) Forging the master alloy bar The rods are powdered by plasma rotating electrode method, and the powder with a particle size of 50-160μm is collected. The powder is mainly spherical, with almost no satellite powder, and there are no obvious defects on the powder surface;

[0065] (2) Laser melting deposition (LMD) was performed on a semiconductor laser system consisting of a Tru Diode 4006 semiconductor laser, an ABB IRB4600 M2004 six-axis joint dynamic hand, and a TWIN10C double-barrel powder feeder. The printed substrate was made of 20 mm thick 30CrMnSiNi2A steel. Deposition was performed in a sealed argon chamber with an oxygen concentration below 100 ppm. During the LMD process, the laser power was 1400 W, the laser scanning speed was 4.8 mm / s, and the overlap rate was 50%. The size of the printed material was 55 mm × 110 mm × 90 mm.

[0066] (3) The printed sample was kept at 950°C for 10 min, then cooled from 950°C to room temperature at a uniform cooling rate of 1°C / s, and then kept at 220°C for 2 h for tempering.

[0067] The properties of the additively manufactured low alloy steel of this embodiment are shown in Table 2 below, achieving a good match between strength and plasticity.

[0068] Example 2

[0069] This embodiment provides an additively manufactured low alloy steel and a preparation method thereof. The components of the steel in this embodiment are shown in Table 1 below. The preparation method is substantially the same as that in Embodiment 1, except that:

[0070] (3) The printed sample was kept at 940°C for 15 min, then cooled from 940°C to room temperature at a uniform cooling rate of 2°C / s, and then kept at 220°C for 2 h for tempering.

[0071] The properties of the additively manufactured low alloy steel of this embodiment are shown in Table 2 below, achieving a good match between strength and plasticity.

[0072] Example 3

[0073] This embodiment provides an additively manufactured low alloy steel and a preparation method thereof. The components of the steel in this embodiment are shown in Table 1 below. The preparation method is substantially the same as that in Embodiment 1, except that:

[0074] (3), the printed sample is kept at 955°C for 15 min, then cooled from 955°C to 350°C at a uniform cooling rate of 2°C / s, then cooled from 350°C to room temperature at a rate of 0.6°C / s, and finally annealed at 220°C for 2 h.

[0075] The properties of the additively manufactured low alloy steel of this embodiment are shown in Table 2 below, achieving a good match between strength and plasticity.

[0076] Example 4

[0077] This embodiment provides an additively manufactured low alloy steel and a preparation method thereof. The components of the steel in this embodiment are shown in Table 1 below. The preparation method is substantially the same as that in Embodiment 1, except that:

[0078] (2), the laser power is 1600 W, the laser scanning speed is 5 mm / s, and the overlap rate is 50%.

[0079] (3), the printed sample was kept at 930°C for 15 min, then cooled from 930°C to room temperature at a uniform cooling rate of 1°C / s, and then kept at 240°C for 2 h for tempering.

[0080] The properties of the additively manufactured low alloy steel of this embodiment are shown in Table 2 below, achieving a good match between strength and plasticity.

[0081] Example 5

[0082] This embodiment provides an additively manufactured low alloy steel and a preparation method thereof. The components of the steel in this embodiment are shown in Table 1 below. The preparation method is substantially the same as that in Embodiment 1, except that:

[0083] In (3), the printed sample is kept at 930°C for 15 min, then cooled from 950°C to 350°C at a uniform cooling rate of 2°C / s, then cooled from 350°C to room temperature at a cooling rate of 1°C / s, and finally annealed at 240°C for 1 h.

[0084] The properties of the additively manufactured low alloy steel of this embodiment are shown in Table 2 below, achieving a good match between strength and plasticity.

[0085] Example 6

[0086] This embodiment provides an additively manufactured low alloy steel and a preparation method thereof. The components of the steel in this embodiment are shown in Table 1 below. The preparation method is substantially the same as that in Embodiment 1, except that:

[0087] (3), the printed sample is kept at 930°C for 15 min, then cooled from 930°C to 350°C at a uniform cooling rate of 1°C / s, then cooled from 350°C to room temperature at a rate of 0.6°C / s, and finally annealed at 240°C for 1 h.

[0088] Figure 1 The microstructure morphology of Example 1 is shown, in which the cellular region in the microstructure of the material can be seen, the cell wall structure divides the original austenite grains, and the rest is composed of lath structure. Figure 2 The electron backscattered image (EBSD) of Example 1 is shown, and it can be seen that the growth of ultra-fine laths is obviously affected by the cell wall area. The actual composition of the cell wall area limits the transformation of austenite to martensite in this area. The martensite structure is actually refined, which improves the strength of the material.

[0089] In the microstructure of the additively manufactured low alloy steel of the embodiment of the present invention, the substructure size of the martensite or martensite / martensite complex structure is significantly refined, and the strength and plasticity of the material are further improved. For example, the length of the lath is 5 to 35 μm. The Cr content at the cell wall is ≥3.0%, and the Mo content is ≥1.1%.

[0090] The properties of the additively manufactured low alloy steel of this embodiment are shown in Table 2 below, achieving a good match between strength and plasticity.

[0091] The inventor has conducted a large number of experimental studies during the research process, and now uses some bad solutions as comparative examples.

[0092] Comparative Example 1

[0093] The alloy composition of this comparative example is the same as that of Example 1. The preparation method of this comparative example is similar to that of Example 1, except that:

[0094] In (3), the printed sample was kept at 950°C for 10 minutes, then cooled from 950°C to room temperature at a uniform cooling rate of 0.5°C / s, and then kept at 220°C for 2 hours for tempering. Some process parameters in the preparation process do not meet the requirements of the present invention.

[0095] Figure 3 The electron backscattered image (EBSD) of comparative example 1 is shown. It can be seen from the figure that due to the slow cooling rate, the effects of cellular segregation and cell wall structure on phase transformation are reduced, and most of the bainite laths can continue to grow through the cellular structure.

[0096] The steel of this comparative example has a yield strength of 1274 MPa, a tensile strength of 1754 MPa, and an elongation of 10.7%.

[0097] Comparative Example 2

[0098] The alloy composition of this comparative example is the same as that of Example 1. The preparation method of this comparative example is similar to that of Example 1, except that:

[0099] In (3), the printed sample was kept at 950°C for 10 minutes, then cooled from 950°C to room temperature at a uniform cooling rate of 50°C / s, and then kept at 220°C for 2 hours for tempering. Some process parameters in the preparation process do not meet the requirements of the present invention.

[0100] The steel of this comparative example has a yield strength of 1331 MPa, a tensile strength of 1771 MPa, and an elongation of 11.5%, and has insufficient strength and plasticity.

[0101] Comparative Example 3

[0102] The alloy composition of this comparative example is the same as that of Example 1. The preparation method of this comparative example is similar to that of Example 1, except that:

[0103] In (3), the printed sample was kept at 950°C for 10 minutes, then cooled from 950°C to room temperature at a uniform cooling rate of 10°C / s, and then kept at 220°C for 2 hours for tempering. Some process parameters in the preparation process do not meet the requirements of the present invention.

[0104] The steel of this comparative example has a yield strength of 1395 MPa, a tensile strength of 1792 MPa, and an elongation of 11.3%.

[0105] Comparative Example 4

[0106] The alloy composition of this comparative example is the same as that of Example 4. The preparation method of this comparative example is similar to that of Example 4, except that:

[0107] In (3), the printed sample was kept at 930°C for 15 minutes, then cooled from 930°C to 350°C at a uniform cooling rate of 1°C / s, then cooled from 350°C to room temperature at a rate of 0.2°C / s, and then kept at 240°C for 1 hour for tempering. Some process parameters in the preparation process do not meet the requirements of the present invention.

[0108] The steel of this comparative example has a yield strength of 1288 MPa, a tensile strength of 1745 MPa, and an elongation of 10.2%.

[0109] Comparative Example 5

[0110] In this comparative example, the alloy composition is calculated by mass percentage as follows: C: 0.27%, Mn: 0.6%, Si: 1.03%, Cr: 2.7%, Ni: 1.0%, Mo: 0.9%, W: 0.1%, Nb: 0.006%, Al: 0.1%, and the balance is Fe and unavoidable impurities. The composition requirements do not meet the requirements of the present invention. The preparation method of the material is the same as that of Example 1.

[0111] The steel of this comparative example has a yield strength of 1410 MPa, a tensile strength of 1825 MPa, an elongation of 8.1%, and relatively poor plasticity.

[0112] Comparative Example 1 uses the same alloy composition as Example 1 and meets the requirements of the present invention. However, the partial cooling rate in the cooling process after high temperature isothermal treatment does not meet the requirements of the present invention, and the cooling is relatively slower, which does not reach the scope of the invention. This is mainly due to the reduced effect of cellular segregation and cell wall structure on phase transformation, and most of the bainite laths can continue to grow through the cellular structure. The material strength is reduced.

[0113] Comparative Example 2 uses the same alloy composition as Example 1 and meets the requirements of the present invention. However, the partial cooling rate in the cooling process after high temperature isothermal does not meet the requirements of the present invention, and the cooling is relatively faster, which does not reach the scope of the invention. Due to the excessive undercooling, the martensitic phase transformation is weakened by the cell-like segregation, and the growth of the lath can also segregate through the cell wall. This results in the coarse size of the lath substructure and a significant reduction in material strength.

[0114] Comparative Example 3 uses the same alloy composition as Example 1 and meets the requirements of the present invention. However, the partial cooling rate in the cooling process after high temperature isothermal does not meet the requirements of the present invention. The cooling is slowed down relative to Comparative Example 2, but it does not reach the scope required by the invention. The growth of the lath is also affected by the cell wall segregation. Although the strength is improved, it still does not reach the scope required by the invention.

[0115] Comparative Example 4 uses the same alloy composition as Example 4 and meets the requirements of the present invention. However, the partial cooling rate during the cooling process after high temperature isothermal treatment does not meet the requirements of the present invention, resulting in the final material properties not meeting the requirements of the present invention.

[0116] In Comparative Example 5, an aluminum content exceeding the requirements of the invention is used. Although the addition of a high content of aluminum is beneficial to the deoxidation of the master alloy rod smelting process, aluminum is easily combined with oxygen to form coarse oxides during the additive manufacturing process. This type of oxide not only does not have a good effect on the strength of the material, but will induce the formation of holes or cracks during the deformation process, resulting in deterioration of the plasticity of the material.

[0117] Table 1 Chemical composition, wt%

[0118]

[0119]

[0120] Table 2 Performance test results

[0121] serial number Yield strength / MPa Tensile strength / MPa Elongation / % Example 1 1450 1865 10.3 Example 2 1465 1849 10.7 Example 3 1374 1857 10.2 Example 4 1354 1835 12.1 Example 5 1480 1878 10.4 Example 6 1373 1834 10.1 Comparative Example 1 1274 1754 10.7 Comparative Example 2 1331 1771 11.5 Comparative Example 3 1395 1792 11.3 Comparative Example 4 1288 1745 10.2 Comparative Example 5 1410 1825 8.1

[0122] Table 3 Microstructure test results

[0123]

[0124]

[0125] The above is only a preferred specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. The alloy design and preparation process of the present invention are also applicable to the additive manufacturing and organization strengthening of alloys with thermodynamic conditions similar to those of the present material, such as different ratios of alloy elements such as carbon, manganese, nickel, chromium, and molybdenum. Any changes or substitutions that can be easily thought of by a technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.

Claims

1. An additively manufactured low alloy steel, characterized in that: The components of the additively manufactured low-alloy steel are, by mass percentage, C: 0.25% to 0.30%, Mn: 0.4% to 0.7%, Si: 0.8% to 1.2%, Cr: 2.4% to 2.8%, Ni: 0.8% to 1.2%, Mo: 0.8% to 1.1%, W: 0.1% to 0.3%, Nb≤0.02%, Al≤0.01%, Ti:≤0.03%, Zr≤0.02%, and the remainder is Fe and unavoidable impurities.

2. The additively manufactured low alloy steel according to claim 1, characterized in that: In the components of the additively manufactured low alloy steel, the Cr / Ni value is controlled to be 2.5-2.

8.

3. The additively manufactured low alloy steel according to claim 1, characterized in that: The microstructure of the additively manufactured low alloy steel consists of a martensite or bainite / martensite multiphase structure with alloy cell segregation.

4. The additively manufactured low alloy steel according to claim 3, characterized in that: Cellular aggregation of alloy elements exists in the microstructure of the additively manufactured low-alloy steel, and the Cr element content at the cell wall is ≥3.0%, and the Mo element content is ≥1.1%.

5. A method for preparing low alloy steel by additive manufacturing, characterized in that: The preparation method is used to prepare the additively manufactured low alloy steel according to any one of claims 1 to 4, comprising: Step S1: preparing powder; Step S2: using laser melting deposition to perform additive manufacturing on the parts, using high-purity argon as the protective gas; after each deposition of a certain thickness, the material is left to cool to room temperature before deposition is performed again; Step S3: Cooling the printed sample to room temperature after high temperature isothermal treatment; Step S4: subjecting the printed sample to low-temperature annealing treatment.

6. The preparation method according to claim 5, characterized in that: In the step S3, the high temperature isothermal treatment includes: keeping the temperature at 930°C to 980°C.

7. The preparation method according to claim 5, characterized in that: In the step S3, during the cooling process, the cooling rate in the temperature range of 850 to 350°C is controlled to be ≥1°C / s; the cooling rate in the temperature range of 350°C to 150°C is controlled to be 0.5°C to 5°C / s.

8. The preparation method according to claim 5, characterized in that: In step S4, the low temperature tempering temperature is controlled to be 210°C to 230°C.

9. The preparation method according to claim 5, characterized in that: In the step S1, the powder is prepared by a plasma rotating electrode method, and the powder particle size is controlled to be 50 to 160 μm.

10. The preparation method according to any one of claims 5 to 9, characterized in that: In the step S2, during the printing process, the laser power is 1400-1800W.